Faktor Yang Mempegaruhi Peningkatan Pendapatan Ibu Dalam Rangka Meningkatkan Kesejahteraan Keluarga : Study Kasus Ibu-Ibu PKK Mawar Wilayah Sukun Kota Malang - Awanto twui wibowo; Ari Nurcahyo Darmawan; Moh. Figo Danuarta (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2022)
In line with the progress of national development as a whole, there is a tendency to increase the role of women in earning a living for the family. From various empirical studies that focus on the study of the workflow of men and women, it turns out that women also play a role in various fields such as agriculture, animal husbandry, crafts, and even industry. According to the findings of the research, the existence of working mothers aims to earn income to help alleviate the family’s economic needs. On average, these mothers contribute 42.4% of their income to the total family income. A total of 72.5% of respondents contribute to their family’s income between 30% and 50%. Meanwhile, they use their leisure time for personal needs, rest, and social activities that aim to socialize.